Analysis of Total Qality Management Implementation of The Cost of Production in Animal Feed Industry - Yulianto Hadi (Accounthink, 2016)
Global competition is forcing companies have the ability to compete with similar companies, especially with companies that have applied science and technology, to be able to win this competition, companies are required to have efficiency so that their products can compete with similar products. To minimize deviations production process and shrinkage fodder, required a series of continuous improvement by the company to support the smooth operation of the company as a whole. Methods of research by the author is a method of collecting data with field studies and literature. Methods of field studies carried out by direct observation to the company. Research conducted an analysis of Total Quality Management. The purpose of this study in order to determine deviations and shrinkage process of production (shrinkage) fodder. The observations were carried out on an on going basis include observation of the moisture content of raw materials, checking the engine used on a regular basis, setting or press machine setup, the engine speed is balanced and improve the existing human resources. From the results of the study authors concluded that the application of Total Quality Management and conduct continuous improvement and sustainable can minimize shrinkage deviations and production process (shrinkage) so that the effectiveness of production can be achieved.